Reasons for variations in the use of open access gastroscopy by general practitioners - Hungin, A P; Bramble, M G; O'Callaghan, H (Gut, 1995)
This study aimed to investigate the wide variation between general practitioners (GPs) in their use of open access gastroscopy by assessing (i) their partnership share, workload, and the aggregated practice request rate; (ii) correlations with their professional and practice characteristics; and (iii) a comparison with referral rates to medicine, surgery, and all specialties. All 145 GPs and their practice managers were sent a questionnaire and hospital held data on all requests for open access gastroscopy over one year were reviewed. During the year, the 145 GPs made 1210 requests for open access gastroscopy, varying from one to 44 per GP. There were 987,880 practice consultations altogether, an average of 22,451 per practice or 7127 per whole time practitioner. Requests for open access gastroscopy formed 2.4% of all referrals, an average of one per 1000 consultations, or eight per GP. Of a total of 49,123 referrals to all specialties (371 per GP) 4218 (8.5%) were to medicine, and 6444 to surgery (13.1%). The following factors did not correlate with requests: vocational training, a concurrent hospital post, length of service, or receipt of the deprivation allowance by the practice. When the open access gastroscopy referral rate was aggregated for each practice the variation between practices was narrowed to essentially twofold. Requests for open access gastroscopy form a small proportion of all referrals (2.4%). Aggregated practice request rates are relatively uniform compared with the wide variation between individual GPs, suggesting a disproportionate gastroenterology workload between partners. The open access gastroscopy service does not seem to be subject to misuse from most GPs if a variation in practice usage is used as a measure.